2016
DOI: 10.21704/rea.v15i2.747
|View full text |Cite
|
Sign up to set email alerts
|

METALES PESADOS EN SUELOS DE PLANTACIONES DE CACAO (Theobroma cacao L.) EN TRES REGIONES DEL PERÚ

Abstract: ResumenEl cacao ha tenido un crecimiento significativo en los últimos años en el Perú y la presencia de metales pesados en los suelos de estas plantaciones es un potencial problema para las exportaciones de este producto. El objetivo del presente estudio fue determinar los contenidos totales de metales pesados (Cd, Ni, Pb, Fe, Cu, Zn, Mn) en los suelos de plantaciones de cacao en las principales áreas de producción del Perú: Zona Norte (Tumbes, Piura, Cajamarca y Amazonas); Zona central (San Martín, Huánuco y … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
2
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 11 publications
(19 reference statements)
4
11
2
8
Order By: Relevance
“…As reported by other studies [16,61], we found a strong correlation between Cd and pH in the soils analyzed here and higher Cd concentrations were evident in alkaline soils in the SM and AM regions. Fertilizers ("Guano de Isla", Sulfomag, dolomite and phosphatic rock) were applied only in the MD and SM regions.…”
Section: Factors Influencing Cadmium Concentrations In Cacao-growing supporting
confidence: 91%
See 1 more Smart Citation
“…As reported by other studies [16,61], we found a strong correlation between Cd and pH in the soils analyzed here and higher Cd concentrations were evident in alkaline soils in the SM and AM regions. Fertilizers ("Guano de Isla", Sulfomag, dolomite and phosphatic rock) were applied only in the MD and SM regions.…”
Section: Factors Influencing Cadmium Concentrations In Cacao-growing supporting
confidence: 91%
“…These values were similar to those found in agricultural soils of cacao plantations in Ecuador [16], but higher than those reported by Arévalo-Gardini et al [61] in cacao plantations from three productive areas of Peru. According to Arévalo-Gardini et al [61], Cd in the soil was absent in the Huànuco region, while it was broadly present in other regions ranging from 0.01 ± 0.02 mg kg −1 (Cajamarca) to 0.53 ± 0.02 mg kg −1 (Piura).…”
Section: Cadmium Content In Soil Of Cacao Plantations From Different supporting
confidence: 89%
“… 1 IPM are referred to integrated pest management that consist in the optimization of cultural practices [ 15 ], such as removal of sick and diseases infested parts of the tree, adequate pruning,and protection of pods with cooper fungicide in the period of pod development (four times per year between December to March). DAP: Diammonium phosphate, PCl: Potassium chloride.…”
Section: Methodsmentioning
confidence: 99%
“…These changes affect the availability of nutrients for growing crops either directly by contributing to the availability of nutrients or indirectly by influencing the physical and chemical environment of the soil [ 13 ]. Agroforestry systems integrate trees with agricultural crops [ 14 ] such as cacao or coffee for example [ 11 , 15 ], and have the potential to enhance soil fertility, maintain the soil organic matter status, promote efficient nutrient cycling, reduce erosion, improve water quality, enhance biodiversity, increase a esthetics [ 14 , 16 ], and over the long-term are also sustainable and appropriate for soil fertility conservation and improve soil health, and sequester carbon [ 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the same way, Arévalo et al [11], mentioned that cocoa had a significant growth in recent years in Peru and the presence of heavy metals in soils of these plantations is a potential problem for exports of this product. The objective of this work was to determine the total quantities of heavy metals (especially Cadmium) in soils of cocoa plantations in the main production areas of Peru.…”
Section: Review Of the Literature Related To The Subjectmentioning
confidence: 90%